2004
DOI: 10.1103/physreve.69.066613
|View full text |Cite
|
Sign up to set email alerts
|

Band structure and omnidirectional photonic band gap in lamellar structures with left-handed materials

Abstract: We theoretically investigate the photonic band structure of one-dimensional superlattices composed of alternating layers of right-handed and left-handed materials (RHM and LHM). The dispersion curves are mainly studied by assuming that the dielectric permittivity and magnetic permeability are constant in each layer. It is shown that such structures can exhibit new types of electromagnetic modes and dispersion curves that do not exist in usual superlattices composed only of RHM. In particular, we emphasize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…is the lattice constant, and c is the light speed in vacuum [11]. It is well known that when any periodic system is limited, k should be complex…”
Section: The Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…is the lattice constant, and c is the light speed in vacuum [11]. It is well known that when any periodic system is limited, k should be complex…”
Section: The Basic Equationsmentioning
confidence: 99%
“…To the best of our knowledge, there is no report regards to the surface modes in L-R PC. Left handed materials in which the dielectric permittivity ε and magnetic permeability µ are simultaneously negative, have received a great deal of attention during the last few years [11]. In our calculations, the dielectric permittivity and magnetic permeability are, in general, assumed to take constant values.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the geometrical parameters of the PCs, the constituent materials types used in the PC have a great impact on their band structure. Optical properties of the PCs of various types of materials such as metals, semiconductors, graphenes, and metamaterials are explored in previous studies [7][8][9][10]. However, PBGs in conventional dielectric PCs strongly depend on the polarization and incidence angle of the electromagnetic waves and this may differ in other types of PCs as well.…”
Section: Introductionmentioning
confidence: 99%
“…The zero-φ eff gap distinguishes itself from a Bragg gap in that it is invariant with a change of scale length and is insensitive to thickness fluctuation. Baria et al [18] have investigated the band structures of one-dimensional superlattices composed of right handed materials and left handed materials. It is shown that such structures can exhibit new type of electromagnetic modes and dispersion curve that do not exist in usual superlattices composed only by right handed materials.…”
Section: Introductionmentioning
confidence: 99%